Konsep Insan Kamil: Studi Komparatif Pemikiran Abdul Karim Al-Jilli dan Muhammad Iqbal - Munawaroh, Umi; Ula, Miftahul (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
This article aims to determine the concept of Insan Kamil from the perspective of Abdul Karim Al-Jilli and Muhammad Iqbal and to compare the concept of Insan Kamil from the perspective of Abdul Karim Al-Jilli and Muhammad Iqbal. This type of research is descriptive qualitative research with library research methods. Data collection techniques used documentation, while in analyzing data, researchers used two analytical techniques, namely content analysis and comparative analysis. The results of the study show that: According to Al-Jilli, Kamil is a servant who always wants to be close to his God by carrying out mystical ascent and spiritual cultivation consisting of 7 maqamat. There are 3 levels of Insan Kamil formulated by Al-Jilli namely al-bidayah, altawassut, and al-khitam. The level of al-khitam or the highest level can only be achieved by Rasulullah SAW. Muhammad Iqbal considers Insan Kamil as a human being who has a strong personality or humility. One's khudi must go beyond 3 stages or criteria to reach the degree of Insan Kamil, namely obedience to God's law, self-mastery, and Divine caliphate. Insan Kamil for Al-Jilli and Iqbal agree as a mirror of a human being who believes and is always close to his God. While the difference between the two is that according to al-Jili the degree of Insan Kamil is obtained through good hablum minallah, whereas according to Iqbal the degree of Insan Kamil is obtained not only through hablum minallah but also hablum minannas.